2021
DOI: 10.1186/s13011-021-00379-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-financial barriers in oral health care: a qualitative study of patients receiving opioid maintenance treatment and professionals’ experiences

Abstract: Background People with substance use disorders often have poor oral health, which can negatively impact their quality of life. Since 2005, patients receiving opioid maintenance treatment (OMT) in Norway have been eligible for free oral health care services offered through public oral health clinics. Despite a large need for oral health services amongst patients in OMT, figures suggest that the use of these services is low amongst this patient group. It has been unclear which barriers that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…These oral health treatment plans should be simple, feasible, centred on client's needs and developed in collaboration with the client. Accessing dental services and regular attendance by AOD service clients have been identified in the literature as key challenges [2,3,11]. To address this, a multidisciplinary care approach is an essential factor in delivering quality dental treatment to priority populations [1,2] including AOD service clients [1].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…These oral health treatment plans should be simple, feasible, centred on client's needs and developed in collaboration with the client. Accessing dental services and regular attendance by AOD service clients have been identified in the literature as key challenges [2,3,11]. To address this, a multidisciplinary care approach is an essential factor in delivering quality dental treatment to priority populations [1,2] including AOD service clients [1].…”
mentioning
confidence: 99%
“…There is little argument that poor oral health is a significant problem among clients of AOD services [1]; and that good oral health is an integral part of overall health, quality of life and wellbeing [2]. Studies have shown that people who use drugs are at increased risk of poor oral health [3] that impacts on their quality of life [2,[4][5][6]. As described in the scoping review, studies of people with substance use disorder (SUD) report high rates of caries, periodontal disease, xerostomia (dry mouth), bruxism, prostheses, toothache and tooth loss [7].…”
mentioning
confidence: 99%
See 3 more Smart Citations